Uji Efek Penurunan Kadar Asam Urat Ekstrak Daun Kelor (Moringa Oleifera Lamk) pada Tikus Putih Jantan Galur Wistar (Rattus Norvegicus) - Rastria Meilanda; Nyimas Nikmah Lanuari (Yayasan Literasi Sains Indonesia, 2023)
Gout is a disease of the residual metabolism of purine substances derived from the rest of the food we consumed. This study used Moringa oleifera Lamk as a treatment for gout. This study aims to know the effect of Moringa oleifera Lamk leaf extract on decreasing uric acid levels in male white rats wistar (Rattus norvegicus). This study used maceration method, using male white rats aged 2-3 months, weighing 100-150 grams. Rats were divided into 10 groups. Each group consisted of 3 rats. Induction given was chicken liver juice as much as 5 ml/200 gBB for 7 days orally.On the 7th day, measurement of uric acid was carried out 6 hours after the last induction. Giving group for negative control was given 1% CMC,for positive control Allopurinol was given, and for giving Moringa leaf extract on fresh and dry leaves dose 2,5 mg/gBB, 4,5 mg/gBB, 9 mg/gBB, 18 mg/gBB every day orally for 7 days. Measurement ofthe decrease in uric acid levels using the Easy Touch® GCU test strip on the 14th day in the 60th, 120th, and 180th minutes. The results showed that freshMoringa(Moringa oleifera Lamk) leaf extract was more effective in reducing uric acid levels in male whitewistar rats (Rattus norvegicus) and dosage which affects the decreasion of uric acid levels in male white rats wistar strain (Rattus norvegicus) is a dose of 18 mg/gBB in the 120th minutes.